Avaliação do status vitamínico A, sarcopenia e condição clínica em idosos institucionalizados - Silva, Janilson Avelino da (2019)
Scholars have shown important changes in the nutritional status of older people living in long-term care facilities for the elderly and draw attention to an adequate nutritional assessment based on conventional methods, such as the use of anthropometric, food consumption and biochemical variables associated with this condition. other predictors of nutritional status verification, such as sarcopenia verification. In this context, this study aims to evaluate vitamin A status, sarcopenia and clinical condition in institutionalized elderly. For this purpose, 105 elderly, ≥60 years old, of both sexes, residing for a period equal to or greater than three months in five (05) Long-term Care Institutions for the elderly of João Pessoa-PB, were selected. Anthropometric assessments (weight, height, body mass index, circumferences and body composition), retinolemia (High Performance Liquid Chromatography), vitamin A intake (food frequency survey of vitamin A source foods), inflammation ( alpha 1 acid glycoprotein - AGP), oxidative stress (total antioxidant capacity-CAT and malondialdehyde MDA), fasting glucose, lipid profile (total cholesterol, triglycerides, high density lipoprotein - HDL-c, non-HDL-c, low density lipoprotein - LDL-c, very low density lipoprotein - VLDL-c, liver function by ALT (alanine aminotransferase) and AST (aspartate aminotransferase), creatinine and urea (markers of renal function) after signing the Informed Consent Form. In addition, the elderly underwent a series of screening tests for sarcopenia.A prevalence of vitamin A insufficiency (<1.05 micromol / L) was found to be 30.5% (32 elderly). Regarding consumption of source foods of vitamin A, 68.6% (72 elderly) of the sample consumed those of animal origin more than 3x / week, while foods of vegetable origin were consumed by 64.8% ( 68 elderly) of the sample, at this same frequency. Multivariate logistic regression analysis showed that schizophrenic individuals are 7.75 (p = 0.00; 95% CI = 2.56-26.59) times more likely to be serum retinol deficient, regardless of other risk factors. . The other variables showed no statistical differences (p> 0.05). Regarding sarcopenia, a prevalence of 37% was found in the sample (37 elderly), with 36% considered severe. Sarcopenic individuals were generally male (p = 0.00; 95% CI = 4.04-46.37), with adequate retinolemia (p = 0.01; 95% CI 0.04-0.63). ) and are overweight (p = 0.04; 95% CI 0.03-0.93), regardless of other risk factors. The other variables showed no statistical differences (p> 0.05). It is concluded that vitamin A deficiency is associated with schizophrenia, regardless of other factors in this study. In addition, being a male is considered an independent risk factor for sarcopenia. While being overweight and having adequate serum retinol concentrations are protective measures against sarcopenia. Thus, a more individualized nutritional assistance is recommended for this population. These results are expected to guide clinical decisions and the development of public policies for the institutionalized elderly population. In addition, early interventions are needed so that older people identified as having a higher risk of vitamin A deficiency and / or sarcopenia can avoid their adverse health consequences.